MATH SOLVE

4 months ago

Q:
# Arrange the steps to solve this system of linear equations in the correct sequence.x + y = -22x – 3y = -9TilesSubtract 3x + 3y = -6 (obtained in step 1) from2x – 3y = -9 (given) to solve for x.Substitute the value of x in the first equation(x + y = -2) to get y = 1.The solution for the system of equations is (-3, 1).x = -15The solution for the system of equations is(-15, 13).Add 3x + 3y = -6 (obtained in step 1) to2x – 3y = -9 (given), and solve for x.x = -3Substitute the value of x in the first equation(x + y = -2) to get y = 13.Multiply the first equation by 3:3(x + y) = 3(-2)3x + 3y = -6.

Accepted Solution

A:

Multiply the first equation by 3

Add 3x+3y=-6 to 2x-3y=-9 to solve for x

Substitute the value of x in the first equation (x+y=-2) to get y=1

The solution for the system of equations is (-3,1)

Add 3x+3y=-6 to 2x-3y=-9 to solve for x

Substitute the value of x in the first equation (x+y=-2) to get y=1

The solution for the system of equations is (-3,1)